Ett minne för livet: A Swedish music collective - Arvidsson, Alf; Adolfsson, Jörgen (Jazz Research Journal, 2012)
Ett minne för livet was a Stockholm-based musicians’ collective of four groups (ISKRA, Spjärnsvallet, Archimedes Badkar, and Vargavinter) that grew out of overlapping memberships and a couple of joint concerts in 1975, and continued to work together into the eighties. They worked together on several levels—arranging concerts and tours; having their own record company; sharing rehearsal premises—and functioned as a pool of musicians. Taking up influences from India, the Balkans and Africa, they deliberately crossed genre borders, mixing styles within concerts/records and within single tunes. In tune to contemporary leftist ideas they were often searching for new ways to play together and to act in relation to their audiences in order to break down hierarchies. They were also active in various political rallies. However, the dominant leftist aesthetics prioritized rock as a musical base, so the collective was rather marginalized even on its primary scenes.